Psychological capital and entrepreneurial success: a multiple-mediated relationship - Juhdi, Noor Hasni (2015)
This study examined the relationship between psychological capital and entrepreneurial success and the roles of entrepreneurial work engagement and entrepreneurial learning intensity as multiple-mediators in influencing the relationship. In addition, the effects of service orientation and market orientation on entrepreneurial factors were also tested. Respondents were the owner-managers of small and medium service enterprises (service SMEs) in Malaysia. Simple random sampling was used, given a sampling frame which contained 502 service SMEs. A questionnaire survey involving 125 entrepreneurs with more than five years of entrepreneurial experience in service businesses provided useful data. The data were analyzed using SPSS and SPSS Macro. The results showed that psychological capital had a positive relationship with entrepreneurial success. In fact, through entrepreneurial work engagement and entrepreneurial learning intensity, the multiple-mediators, the relationship was found to be more comprehensive. Application of bootstrapping procedure in SPSS Macro had found that entrepreneurial work engagement and entrepreneurial learning intensity were simultaneously significant multiple-mediators but entrepreneurial work engagement had higher impact than entrepreneurial learning intensity on the relationship between psychological capital and entrepreneurial success. In conclusion, this study supported the theoretical arguments that entrepreneurial success are strongly associated with internal power and strengths, which this study believed as psychological state resources. However, the relationships between firm orientations such as service and market orientations and entrepreneurial factors require further investigation in future studies.